(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article examines the interconnection between communicative taboos religion and beliefs, gives the examples of word, topic and contact taboos in Ukrainian proverbs and sayings.